The relationship between work stress and quality life among Indonesian health workers during the COVID-19 pandemic - Paschalia, Yustina P. M.; Doondori, Anatolia K.; Kurnia, Theresia Avila; Seto Se, Bonaventura R. (Public Health of Indonesia, 2022)
Background: During the COVID-19 pandemic, health workers are directly involved in many healthcare activities. If the pandemic lasts for a long time, the situation of ambiguity and full of threats will be unimaginable. It will potentially worsen individual emotions, increase work stress, and affect the quality of life of health workers. Objective: To identify relationships between work stress levels and quality of life for health workers during the COVID-19 pandemic. Methods: A cross-sectional design was used in this study, involving 90 health workers in a public health center in Ende Regency, East Nusa Tenggara Province, Indonesia, selected using total sampling. WHOQOL – BREF questionnaire and Stress Scale were used to collect data. Descriptive statistics and Chi-square were used for data analysis. Result: Most respondents did not experience work stress (77.8%) and had a good quality of life (93.3%). There was a significant relationship between work stress and the quality of life of health workers during the COVID-19 pandemic (p <0.001). Conclusion:  Work stress is a significant factor influencing the quality of life. Therefore, interventions to reduce the stress level of the health workers are necessary.